The Impact of Organizational and National Cultural Differences on Social Conflict and Knowledge Transfer in International Acquisitions - Vaara, Eero; Sarala, Riikka; Stahl, Günter K.; Björkman, Ingmar (Journal of Management Studies, 2012)
abstractThe purpose of this paper is to elucidate the effects of organizational and national cultural differences on international acquisitions. We argue that cultural differences prompt social identity building that leads to ‘us versus them’ thinking and thereby creates the potential for social conflict. We also maintain that the same cultural differences can contribute to learning in terms of knowledge transfer. We develop a structural equation model to test these hypothesized effects on a sample of related international acquisitions. Our analysis shows that cultural differences at the organizational level are positively associated with social conflict, but that national cultural differences can decrease social conflict. Furthermore, both organizational and national cultural differences are positively associated with knowledge transfer. This analysis shows the importance of disentangling the various effects that cultural differences have on international acquisitions. It also suggests that national cultural differences are less of a problem in international acquisitions than is usually assumed.